Novelties and limitations of tissue-engineered materials in treating traumatic nerve injuries: a mini review - Deininger, Stefanie; Knoll, Andreas; Grübel, Nadja; Pala, Andrej; König, Ralph; Wirtz, Christian Rainer; Pedro, Maria Teresa (Frontiers in Cell and Developmental Biology, 2025)
Peripheral nerve injuries remain challenging due to the limited regenerative capacity over long distances and the complexity of repair mechanisms. While autologous nerve grafts are the clinical gold standard, their use is restricted by donor-site morbidity and tissue availability. Tissue-engineered materials such as nerve guidance conduits (NGCs), hydrogels, and bioactive scaffolds offer alternative solutions by providing structural support and delivering trophic, immunomodulatory, or electrical cues. This mini-review categorizes these materials by their functional properties, including drug delivery, cell integration, and electroactivity, and critically assesses their preclinical performance and translational limitations. Natural materials such as collagen and chitosan exhibit good biocompatibility but limited mechanical stability and variability. Synthetic polymers and electroactive materials allow for customization and controlled stimulation but often provoke immune responses or degrade into harmful byproducts. Advanced drug-delivery systems using hydrogels and microspheres enable targeted factor release, yet reproducibility and kinetics remain critical barriers. Cell-integrated constructs, including Schwann cell-like cells and engineered neural tissue, offer high regenerative potential but face challenges in scalability, regulatory classification, and manufacturing. Importantly, many preclinical studies do not benchmark against autografts or address neuroma formation, fibrosis, and delayed regeneration—key issues in human lesions. A summary of preclinical constructs and translational barriers is provided to highlight recurring obstacles such as immune incompatibility, insufficient vascular integration, and regulatory hurdles. Future research must refine model systems, align regulatory strategies, and enhance construct functionality to enable effective clinical translation.